The Relationship of Drug Therapy Problems and Outcome Therapy in Tuberculosis Patients in Surabaya Health Center - Wijaya, I Nyoman; Nathganeila, Luthfia Andini; Priyandani, Yuni (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2024)
Background: Tuberculosis (TB) is a highly contagious disease and is difficult to eradicate in Indonesia. Indonesia ranks second in the number of TB sufferers in the world. Generally, TB patients use more than two types of drug therapy it can affect the drug therapy problems that arise and can affect the success of treatment.Objectives: This study aims to see the effect of the number of drugs used by TB patients on the number of drug therapy problems (DTP) and therapy outcomes in tuberculosis patients.Methods: This study was a cross-sectional study with purposive sampling conducted at health centers in the Surabaya area in January- June 2024. The sample inclusion criteria included pulmonary tuberculosis patients who had undergone treatment for over one month, were not less than 17, and could communicate well using a guided interview method.Results: The results showed that the number of patients who participated in the study was 110 people. Most patients used 4 types of drugs (30.0%). Most (30.0%) had two DTPs. Spearman's relationship test between the number of drugs and the number of DTPs with a p-value = 0.000 and a correlation coefficient of 0.472. Spearman's relationship test between the number of DTP and the outcome therapy with a p-value = 0.430 and a correlation coefficient of -0.076.Conclusion: From this study, it can be concluded that there is a significant relationship between the number of drugs and the number of DTPs in TB patients and there is no relationship between RTP and therapeutic outcomes in TB patients.